The impact of torture on mental health in the narratives of two torture survivors - de la Rie, Simone M.; Bos, Jannetta; Knipscheer, Jeroen; Boelen, Paul A (Torture Journal, 2018)
Introduction: Torture survivors risk developing Posttraumatic Stress Disorder (PTSD) as well as other mental health problems. This clinical case study describes the impact of torture on two survivors who were treated for their PTSD with Narrative Exposure Therapy. Methods: The reports of the narratives of two torture survivors were qualitatively analyzed. It was hypothesized that torture yields overaccommodating cognitions, as well as mental defeat, which in turn, are related to severity of psychological complaints. Results: Both patients have experienced an accumulation of traumatic events. The psychological and physical torture they experienced lead to increased anticipation anxiety, loss of control and feelings of hopelessness, as well as overaccommodating cognitions regarding self and others. Conclusions: Cognitions, culture and beliefs, as well as issues of confidence and a more long-term perspective affect therapeutic work. Building trust, pacing the therapeutic process, and applying tailor-made interventions that focus on cognitions regarding self-esteem, trust in relationships, as well as safety and control are warranted.